Cost-Effectiveness Analysis of Two or Three Dosage Forms of N-Acetylcysteine in ICU Patients with Pneumonia - July; Sri Teguh Rahayu; Aura Febri Khairani (Jurnal FARMASIMED (JFM), 2025)
Background: Pneumonia is an acute infection of the lung tissue caused by various microorganisms, exposure to chemicals, or physical lung damage. The mucolytic N-acetylcysteine (NAC), administered in varying numbers of dosage forms, is frequently used as an adjunctive therapy in the management of pneumonia. Objective: This study evaluated the cost-effectiveness of N-acetylcysteine (NAC) mucolytic therapy using two versus three NAC dosage forms in ICU patients with comorbid pneumonia, by analyzing clinical improvement, ICU length of stay, and drug costs. Methodology: A retrospective observational study was conducted at the Prof. Dr. dr. Mahar Mardjono National Brain Center Hospital, involving medical record data from 88 pneumonia patients, who received two or three NAC dosage forms. Result: Of the patients, 51.1% had a length of stay (LOS) exceeding 9 days, with a higher proportion in the three-dosage-form group (73.7% vs. 45.0%, P = 0.083). Medical records and radiological findings indicated greater clinical improvement in the three-dosage-form group (31.6% vs. 16.0%, P = 0.001). The Average Cost-Effectiveness Ratio (ACER) was Rp20,932 for two dosage forms and Rp27,961 for three dosage forms per 1% effectiveness, demonstrating a lower cost per unit of effectiveness for two dosage forms. The Incremental Cost-Effectiveness Ratio (ICER) was Rp35,169 per 1% additional effectiveness, with an additional cost of Rp548,637 for a 15.6% effectiveness increase in the three-dosage-form group. Conclusion: Therapy with three dosage forms of N-acetylcysteine yields better clinical improvement compared to two dosage forms, but is associated with a longer ICU length of stay and higher drug costs.